A survey of quality control position in selected garment buying offices - Wong, Jacqueline N.
This study is about the Quality Control (QC) positions in buying offices in Metro Manila. Its purpose is to provide a profile of the Quality Control positions existing in buying offices that would help BS Clothing Technology graduates prepare for a career in the Quality Control field. Data were gathered from 29 Quality Controllers and twelve personnel manages using two sets of questionnaires. Some data were also obtained through observations and interviews during the researcher's on-the-job-training in one of the buying office that participated in this study. The researcher was exposed to the skills required to perform Quality Control functions and other QC related activities. After comparing and analyzing the data gathered from the personnel managers and from the Quality Controllers, this study revealed that there are work experiences, educational, personal, and human relation skills required for the Quality Control positions in buying offices. Also, Quality Controllers of these buying offices have similar and different tasks. In the same way, the required qualifications for these positions vary. All of these buying offices require that their Quality Controller must have knowledge on Quality Control standards, specifications of the garments and possess communication skills proficiency. However, these buying offices require different number of years of work experience (in relation to Quality Assurance/Control and to supervisory position), educational attainment (majority of the buying office require college degree), technical knowledge in production, and interpersonal skills. Data about the training, development and evaluation process for Quality Control job in buying offices were also obtained. The gathered information provided insights on how to train and develop an effective and efficient Quality Controller.